Apocalyptic Vision in J. G. Ballard’s “Billennium”: An Eco-critical Study - Nepal, Neelam (Prāgyik Prabāha, 2023)
G. Ballard’s “Billennium” presents apocalyptic consciousness. This paper argues that Ballard uses the rhetoric of apocalypse to visualize the impending disaster caused by the problem of overpopulation. It attempts to analyze the story in the light of Friedrich Buell, Greg Garrard and Lawrence Buell’s concept of apocalypse within environmental discourses. The nature of apocalypse in the story is not the usual presentation of violent or cataclysmic end of everything but comic in the sense that it ‘unveils’ or ‘uncovers’ the weaknesses and follies of human beings such as greed for money and power that are responsible for the looming threats of the problem of overcrowding and loss of space in the near future.